The Use of Robotic Technology in Female Pelvic Floor Reconstruction (Springer International Publishing, 2018)
This text is designed to present a comprehensive and state-of the-art approach to robotic female pelvic reconstructive surgery. Written by experts in both urology and urogynecology, each of these sections address patient selection, pre-operative considerations, surgical technique, and management of intra and post -operative complications. Furthermore, each chapter includes the most current evidence in the literature that supports specific techniques. Extensive illustrations make this an interactive text. Emphasis is placed on sacrocolpopexy, the mostly commonly performed robotic procedure performed in female pelvic medicine. The set up of this operation, surgical technique, and tips and tricks are discussed. In addition, the management of the uterus is also be addressed in detail, including supracervical and total hysterectomy, as well as uterine-sparing techniques. The appropriate preoperative evaluation, including decisions to be made in addressing concomitant surgical conditions such as stress urinary incontinence, is addressed so that the reader can prov ide comprehensive management for all surgical pelvic floor disorders. Other reconstructive procedures covered include controversial topics such as power morcellation of the uterus and placement of vaginal mesh. The text will also include elements that pertain to male and female patients, such as ureteral reimplantation and sigmoid resection. The Use of Robotic Technology in Female Pelvic Floor Reconstruction will be invaluable to both urologists and gynecologists in the field.